2021
DOI: 10.1136/bmjopen-2020-040336
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding complications of thromboprophylaxis with dabigatran, nadroparin or rivaroxaban for 6 weeks after total knee arthroplasty surgery: a randomised pilot study

Abstract: ObjectivesFor the non-vitamin-K oral anticoagulants, data on bleeding when used for 42 days as thromboprophylaxis after total knee arthroplasty (TKA) are scarce. This pilot study assessed feasibility of a multicentre randomised clinical trial to evaluate major and clinically relevant non-major bleeding during 42-day use of dabigatran, nadroparin and rivaroxaban after TKA.Patients and methodsIn 70 weeks, between July 2012 and November 2013, 198 TKA patients were screened for eligibility in the Martini Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…However, anticoagulant chemoprophylaxis puts patients at risk for bleeding after TKA. Bleeding complications (including ecchymosis) following total joint arthroplasty are not acceptable, as they can lead to more important complications, such as infection, wound healing problems, dysfunction and loosening of the joints, with a high likelihood of affecting the surgical outcome ( 20 ). Rivaroxaban, a direct oral factor Xa inhibitor, is commonly prescribed for the prevention of VTE after TKA due to its effectiveness, high safety and convenience of use ( 3 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, anticoagulant chemoprophylaxis puts patients at risk for bleeding after TKA. Bleeding complications (including ecchymosis) following total joint arthroplasty are not acceptable, as they can lead to more important complications, such as infection, wound healing problems, dysfunction and loosening of the joints, with a high likelihood of affecting the surgical outcome ( 20 ). Rivaroxaban, a direct oral factor Xa inhibitor, is commonly prescribed for the prevention of VTE after TKA due to its effectiveness, high safety and convenience of use ( 3 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Effective perioperative and postoperative management is a hot issue for its importance of improving recovery and reducing complications after THA or TKA, 43,44 while complications including thromboembolism, bleeding and infection remain the major causes of delayed functional rehabilitation. Thus, how to minimize the risk of thromboembolic events while not placing the patient at an increased risk for wound complications associated with anticoagulation is a major research focus for orthopaedic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved 1683 studies from 3 databases, of which 20 studies published between 2006 and 2021 were finally eligible for inclusion. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Figure 1 shows the detailed study selection process and results. The detailed information of the included studies is showed in Table 1.…”
Section: General Information About the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our SUCRA probabilities showed that nadroparin performed best in decreasing the risk of bleeding. A recent pilot study indicates that nadroparin, in comparison with dabigatran or rivaroxaban, showed no difference in bleeding complications in patients with total knee arthroplasty surgery (van der Veen et al, 2021). A retrospective study compared the safety and efficacy of tinzaparin and nadroparin in neurosurgery and showed no significant difference in bleeding events and incidence of VTE (Wilhelmy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%